Isolation and characterization of dnaJ null mutants of Escherichia coli. - Sell, S M (1990)
Bacteriophage lambda requires the lambda O and P proteins for its DNA replication. The rest of the replication proteins are provided by the Escherichia coli host. Some of these host proteins, such as DnaK, DnaJ, and GrpE, are heat shock proteins. Certain mutations in the dnaK, dnaJ, or grpE gene block lambda growth at all temperatures and E. coli growth above 43 degrees C. We have isolated bacterial mutants that were shown by Southern analysis to contain a defective, mini-Tn10 transposon inserted into either of two locations and in both orientations within the dnaJ gene. We have shown that these dnaJ-insertion mutants did not grow as well as the wild type at temperatures above 30 degrees C, although they blocked lambda DNA replication at all temperatures. The dnaJ-insertion mutants formed progressively smaller colonies at higher temperatures, up to 42 degrees C, and did not form colonies at 43 degrees C. The accumulation of frequent, uncharacterized suppressor mutations allowed these insertion mutants to grow better at all temperatures and to form colonies at 43 degrees C. None of these suppressor mutations restored the ability of the host to propagate phage lambda. Radioactive labeling of proteins synthesized in vivo followed by immunoprecipitation or immunoblotting with anti-DnaJ antibodies demonstrated that no DnaJ protein could be detected in these mutants. Labeling studies at different temperatures demonstrated that these dnaJ-insertion mutations resulted in altered kinetics of heat shock protein synthesis. An additional eight dnaJ mutant isolates, selected spontaneously on the basis of blocking phage lambda growth at 42 degrees C, were shown not to synthesize DnaJ protein as well. Three of these eight spontaneous mutants had gross DNA alterations in the dnaJ gene. Our data provide evidence that the DnaJ protein is not absolutely essential for E. coli growth at temperatures up to 42 degrees C under standard laboratory conditions but is essential for growth at 43 degrees C. However, the accumulation of extragenic suppressors is necessary for rapid bacterial growth at higher temperatures.